Necessity of Translating the Ghana National Anthem into Indigenous Languages - Mensah, Timothy; Essel, Bright; Sam, George; Afful, Samuel Kwame; Okyere, Dennis Amakye (Integrated Journal for Research in Arts and Humanities, 2023)
National anthems are an integral part of every country's identity and heritage. The national anthem represents a country's culture, history, and traditions. However, in many countries, the official anthem is only available in one language, usually the dominant language spoken by most of the population. This exclusionary approach denies linguistic diversity and undermines the cultural rights of minority groups, particularly indigenous communities who are illiterates. In this research paper, we argue that it is necessary to translate the Ghana national anthem into indigenous languages to promote linguistic and cultural diversity, preserve cultural heritage, and promote social inclusion as well as give fundamental human right to language to those Ghanaians who are not able to read and write in the English language. The paper examines case studies of countries that have already taken steps in this direction and evaluate the impact of translating the official anthem into indigenous languages.